2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037614
|View full text |Cite
|
Sign up to set email alerts
|

A body position influence on ECG derived respiration

Abstract: An influence of a human body position on ECG derived respiration (EDR) signal is presented in the paper. Examinations were performed during deep, suspended and normal breathing for eight people in four different body positions. EDR and thoracic impedance signals were compared using correlation and standard deviation coefficients. Obtained results have shown that it is possible to monitor breath activity of people being in different position, however a precise interpretation of the obtained signal is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The OBF database can be used as a benchmark for: 1) Evaluating the methods of physiological signal derivation (HR, HRV and RF) from facial videos (of restingstate vs. post-exercise; or of three groups of different skin tones); 2) Training computational models to use video-extracted physiological features for AF detection. We also carry out experiments on OBF database to: 1) Evaluate the accuracy of HR, HRV and RF measurement from face, and report the performance as baseline results for future comparison with other proposed methods; 2) Use the face-extracted HRV features for detecting AF cases [16].…”
Section: Contribution Of the Current Studymentioning
confidence: 99%
“…The OBF database can be used as a benchmark for: 1) Evaluating the methods of physiological signal derivation (HR, HRV and RF) from facial videos (of restingstate vs. post-exercise; or of three groups of different skin tones); 2) Training computational models to use video-extracted physiological features for AF detection. We also carry out experiments on OBF database to: 1) Evaluate the accuracy of HR, HRV and RF measurement from face, and report the performance as baseline results for future comparison with other proposed methods; 2) Use the face-extracted HRV features for detecting AF cases [16].…”
Section: Contribution Of the Current Studymentioning
confidence: 99%
“…A basic drawback of this explanation is the impossibility of interpreting the EDR signal in terms of its phase in reference to a direct recording of airflow [1], [5]. Moreover, the phase difference between these signals depends on the lead configuration [8], [16]. On the other hand, there are studies supporting the hypothesis that the heart movement induced by respiration activity is more complex than rotation only, [23]- [25].…”
Section: Discussionmentioning
confidence: 99%
“…The value of the phase shift differed between the studies however, the reason for this was not explained or even discussed. An analysis of the data presented in the literature suggested that this phase could depend on electrode lead configuration and body position [8]. Thus, it could be driven that aside the heart electrical dipole rotation there are also other mechanisms responsible for EDR signal.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the measurement properties of the capacitive electrode, the lead configuration used is also important. When considering the application of the method with systems built into furniture, e.g., an armchair or a chair, the most commonly used is a lead analogous to the first Eindhoven one, but with electrodes placed in the area of the back and at different heights below the shoulders [ 22 , 23 ]. On the other hand, the ECG lead referred to as monitoring is widely used in many applications.…”
Section: Introductionmentioning
confidence: 99%